(3JShjI GdefGRYGJ ai GdChQGb GdeGdjI (B/ s - (3SdWGf Hf aQGL QTjO GdSHjYi s; (3eMeO HgLJ YHOGddg bGjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2009)
(3JJfGhd gPg GdQSGdI ehVhY JShjI efGRYGJ GdChQGb GdeGdjI MjK jNUU dgG JegjOi HYfhGf EUOGQ GdChQGb GdeGdjI hcjajI JOGhdgG hjhVM CfhGYgG GdJbdjOjI hGdMOjKI hLgGJ EUOGQgG hcjajI JOGhdgG hjJfGhd GdWQb GdeJHYI ai JShjI Jdc GdefGRYGJ hgi dLfI Shb GdeGd ef MjK GNJUGUGJgG hWHjYJgG GdbGfhfjI hGdMdhd GdhOjI daV GdefGRYGJ hgi (B: (3GdeaGhVI hGdJhajb hGdhSGWI hGdJMcje HjfeG jYQV cPdc cjajI JfajP GJaGbjGJ hCMcGe JMcje GdChQGb GdeGdjI heHQQGJ GdYhOI ddbhGYO GdYGeI HTCf GdefGRYGJ eMd GdMOjK GdJi JQLY Edi fXGe Yed GddLfI GdePchQI hEdi CSdhH GdJMcjes
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2009s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B303-314s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdChQGb GdeGdjIs; (3JShjI GdefGRYGJ s; (3NUGFU GdChQGb GdeGdjIs; (3GdCSges; (3GdSfOGJs; (3gjFI GdQbGHI GdeGdjIs; (3GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs